Biocompatibility and antimicrobial efficacy of iodine-supported titania nanotubes on 3D-printed Ti-6Al-4V implants - Pariwat Taweekitikul; Abdul Azeez Abdu Aliyu; Nanthawan Jinakul; Amaraporn Wongrakpanich; Chedtha Puncreobutr; Jirapon Khamwannah; Boonrat Lohwongwatana; Saran Tantavisut (PLoS ONE, 2025)
Implant-associated infections (IAI) are a significant concern within the field of orthopedics. To develop an implant with antimicrobial properties, titania nanotubes (TNTs) supported with iodine were synthesized on 3D-printed Ti-6Al-4V implants using the electrochemical anodization (ECA) technique. This study aims to analyze the release profile of iodine and the antimicrobial efficacy and cytotoxicity of the iodine-supported TNT (I-TNTs) on the 3D-printed Ti-6Al-4V implant. 3D-printed Ti-6Al-4V samples were doped with six different iodine formulations, including four test groups containing TNT and two control groups without TNT. As printed 3D Ti-6Al-4V samples and TNTs samples without iodine were also utilized as control groups. In vitro assays were performed to assess the drug elution, cytotoxicity, and antimicrobial efficacy. All tested I-TNTs samples exhibited sustained iodine release over 28 days without an initial burst. Notably, the amount of iodine released from I-TNTs was significantly higher compared to the control group. TNTs with a higher aspect ratio (AR) and the ECA process using higher potassium iodide (KI) concentration were found to have better cumulative iodine release profiles. No cytotoxicity was observed when tested against the mouse calvaria-derived preosteoblast cell line (MC3T3-E1). The antibacterial property of the implant surface became evident within 24 hours, with complete inhibition of S. aureus and MRSA in I-TNTs samples. This innovative approach is an intriguing alternative for preventing infections on 3D-printed Ti-6Al-4V implants.